Respuesta :

Answer:

s  = -70 in the given expression.

Step-by-step explanation:

Here, the given expression is:

[tex]\frac{s}{3} - \frac{7}{6} + \frac{2s}{5} = \frac{3s}{4}[/tex]

Now, to find the value of s, we need to simplify the given expression:

We get:

[tex]\frac{s}{3} - \frac{7}{6} + \frac{2s}{5} = \frac{3s}{4}\\\implies \frac{s}{3}  + \frac{2s}{5} -  \frac{3s}{4}  = \frac{7}{6}\\\implies\frac{20(s) + 12(2s) - 15(3s)}{60}    = \frac{7}{6}\\\implies \frac{20 s  + 24 s - 45 s}{60}   = \frac{7}{6}\\\implies \frac{-s}{60} = \frac{7}{6}\\\implies s = \frac{7}{6} \times (-60)  = - 70\\\implies s  = (- 70)[/tex]

Hence, s  = -70 in the given above expression.